Smart villages in the EU and beyond - Visvizi, Anna; Lytras, Miltiadis D.; Mudri, György (Bingley, U.K. : Emerald Publishing Limited, 2019)
Written by leading academics and practitioners in the field, Smart Villages in the EU and Beyond offers a detailed insight into issues and developments that shape the debate on smart villages, together with concepts, developments and policymaking initiatives including the EU Action for Smart Villages.This book derives from the realization that the implications of the increasing depopulation of rural areas across the EU is a pending disaster. This edited collection establishes a framework for action today, which will lead to sustainable revitalization of rural areas tomorrow.Using country-specific case studies, the chapters examine how integrated and ICT-conscious strategies and policy actions focused on wellbeing, sustainability and solidarity could provide a long-term solution in the revitalization of villages across the EU and elsewhere. Best practices pertinent to precision farming, energy diversification, tourism, entrepreneurship are discussed in detail.As an in-depth exploration of the Smart Village on a multinational scale, this book will serve as an indispensable resource for students, researchers and policy leaders in the fields of politics, strategic management and urban and rural studies.
Prelims -- Smart villages: relevance, approaches, policymaking implications -- Integrated approach to sustainable EU smart villages policies -- Smart villages revisited: conceptual background and new challenges at the local level -- Toward a new sustainable development model for smart villages -- The role of leader in smart villages: an opportunity to reconnect with rural communities -- Precision agriculture and the smart village concept -- Energy diversification and self-sustainable smart villages -- The role of smart and medium-sized enterprises in the smart villages concept -- Smart villages in Slovenia: examples of good pilot practices -- Smart village projects in Korea: rural tourism, 6th industrialization, and smart farming -- Smart villages and the GCC countries: policies, strategies, and implications -- Smart villages: mapping the emerging field and setting the course of action -- Index.
Includes index.
Print version record.
Keywords: Rural development -- European Union countries; Sustainable development -- European Union countries; Political Science -- Public Policy -- Environmental Policy; Politics & government